ACCOUNTING MEASUREMENT UNDER SOCIAL RESPONSIBILITY AND ITS REFLECTION ON PERFORMANCE AND COMPANY VALUE-APPLIED STUDY IN A SAMPLE OF IRAQI INDUSTRIAL COMPANIES - Ahmed Rahi Abed; Zina Adnan Kareem; Maytham Hazim Azeez Khzaee (American Journals, 2024)
The purpose of the study is to clarify how social responsibility accounting contributes to a company's increased value. To this end, concepts of social responsibility, accounting for social responsibility, and company value are defined, and the significance of social responsibility accounting disclosure in the financial statements of industrial companies listed on the Iraq Stock Exchange is stated. By using information from the yearly financial reports of a sample of Iraqi industrial businesses registered on the Iraq Stock Exchange a total of twenty-five companies finance seeks to increase the value of the company. where a sample of those businesses in total was chosen, and the sample accounted for 84% of the study population between 2011 and 2020. The study's practical results include the finding that each of the six independent factors significantly affected the company's worth at various points. Regarding the research's suggestions, the most notable one is that industrial company managements need to be made aware of the significance of their commitment to disclosing social responsibility.